বাংলাদেশের তেল-গ্যাস : কার সম্পদ কার বিপদ? - মুহাম্মদ, আনু. (ঢাকা : জাতীয় গ্রন্থ প্রকাশন, 2002)
On the prospects of the gas industry of Bangladesh and policies of the Government of Bangladesh affecting it.
Includes bibliographical references.
In Bengali.
Keywords: Gas industry -- Bangladesh; Gas industry -- Government policy -- Bangladesh